Surrogates of immunologic cell death (ICD) and chemoradiotherapy outcomes in head and neck squamous cell carcinoma (HNSCC). (July 2019) - Economopoulou, Panagiota; Koutsodontis, George; Strati, Areti; Kirodimos, Efthymios; Giotakis, Evangelos; Maragoudakis, Pavlos; Prikas, Constantine; Papadimitriou, Nikolaos; Perisanidis, Christos; Gagari, Eleni; Kotsantis, Ioannis; Vagia, Elena; et al.
Highlights: Analysis of TLR expression on CTCs of patients with HNSCC is feasible. Chemoradiation leads to quantifiable effects in surrogate markers of ICD. CXCL10 has prognostic effect in HNSCC patients treated with chemoradiation. Abstract: Objectives: Chemoradiation can induce immunogenic (ICD) or tolerogenic cell death. ICD relies on the generation of damage-associated molecular patterns which can stimulate toll-like receptors (TLRs). We sought to determine whether we can predict responses to chemoradiation by measuring surrogate biomarkers of ICD in a cohort of patients with locally advanced (LA) head and neck squamous cell carcinoma (HNSCC). Materials and Methods: In a cohort of 113 LA HNSCC pts we evaluated expression of TLR4, TLR7 and TLR9 in the EpCAM + circulating tumor cell (CTC) fraction at baseline and after cisplatin chemoradiation. We also quantified changes in chemokines CXCL10, CXCL16 and IL-2R in the serum. Results: Seventy three patients had evaluable specimens. Among cases with biomarker assessment at baseline and post treatment, 36.8% had an increase in CXCL10 levels (p = 0.022), 73.7% had an increase in CXCL16 levels (p = 0.002) and 63.8% had an increase in IL2Ra levels (p = 0.032) with treatment. 52.0% of evaluable cases at baseline and post-treatment had an increase in TLR4 levels (p = 0.996), 42.9% had an increase in TLR7 levels (p = 0.042) and 27.7% had increase in TLR9 levels (p = 0.011) with treatment. CXCL10 levels at baseline were significantly associated with PFS and OS (p = 0.010 and p = 0.032, respectively). Conclusions: Our results suggest that chemoradiation leads to quantifiable effects in surrogate markers of ICD. These effects may inform trials combining chemoradiation with immune checkpoint inhibitors. In addition, CXCL10 has prognostic effect in pts treated with chemoradiation.